Impact of patient education by nurse case managers on decision making for out-of-pocket anti-osteoporotic pharmaceutical therapy: a single-center retrospective study - Ya-Lian Deng; Hsu-Tung Lee; Shih-Yi Lin; Tan-Hsiu Liao; Chia-Tien Hsu (BMC, 2024)
Abstract Background Osteoporosis is a common condition that increases the risk of fracture and mortality. In Taiwan, clinical guidelines recommend pharmaceutical therapy for patients with a T-score of ≤ − 2.5; however, Taiwan's National Health Insurance (NHI) only covers these medications for those with a history of fragility fractures. This gap in coverage necessitates a discussion of out-of-pocket treatment options. To address this, we provided an integrated care program with patient education and shared decision-making by nurse case managers specializing in osteoporosis. We evaluated whether education by nurse case managers influences patients with a T-score ≤ − 2.5, who are not covered by the NHI, to choose out-of-pocket pharmaceutical therapy. Methods We retrospectively reviewed medical records of patients who underwent bone density scanning at our hospital between January 2014 and December 2021. We identified 4,462 patients with a T-score of ≤ − 2.5 who were ineligible for NHI-covered anti-osteoporotic therapy and analyzed trends in out-of-pocket medication use. Since the integrated care program began in 2018, we evaluated whether education by nurse case managers between 2018 and 2021 influenced patients' decisions to pay out-of-pocket for therapy. After the implementation of the integrated care program, we identified 2,910 patients with a T-score ≤ -2.5 who were ineligible for NHI-covered anti-osteoporotic therapy. Of these, 640 opted for out-of-pocket treatment, while 2,270 chose conservative care. After a 1:1 propensity score match based on age and sex, logistic regression was used to analyze the impact of nurse case manager education on these decisions. Results Between 2014 and 2021, 888 of the 4,462 patients chose out-of-pocket pharmaceutical therapy. Before the implementation of the integrated care program and patient education by nurse case managers (2014-2017), 16% of the patients opted to pay out-of-pocket for anti-osteoporotic therapy. After the program was implemented (2018-2021), the rate increased significantly to 22% (P < 0.001). A multivariate logistic regression model showed that a history of osteoarthritis (adjusted odds ratio = 1.576; P = 0.009) and education provided by the nurse case managers (adjusted odds ratio = 5.044; P < 0.001) were significantly associated with choosing out-of-pocket therapy. Conclusions Education from nurse case managers significantly increased the likelihood of patients choosing out-of-pocket anti-osteoporotic therapy in our hospital, thereby bridging the gap between clinical guidelines and NHI reimbursement criteria.